IceCube Enhanced Hot Water Drill functional description. Issue 68 (2014) - Benson, T.; Cherwinka, J.; Duvernois, M.; Elcheikh, A.; Feyzi, F.; Greenler, L.; Haugen, J.; Karle, A.; Mulligan, M.; Paulos, R.
Abstract: The IceCube Neutrino Observatory was constructed at the South Pole during the 2004/05 to 2010/11 austral summer seasons. IceCube transforms 1 km 3 of Antarctic ice into an astrophysical particle detector composed of 86 cables (strings) of optical sensors buried deep beneath the surface. Each string required drilling a borehole ∼60 cm in diameter to a depth of 2500 m. The 5 MW Enhanced Hot Water Drill was designed and built specifically for this task, capable of producing the required boreholes at a rate of one hole per 48 hours. Hot-water drilling on this scale presented unique challenges and was rich in lessons learned, yielding a collection of notable developments and takeaways (e.g. fuel-saving measures, thermal modeling, firn drilling and closed-loop computer control). Descriptions of system functionality and of lessons learned from IceCube drilling are presented.